Pyogenic granuloma - report of three cases in rare sites - Sulabha, AN; Choudhari, S; Suchitra, G (Bangladesh Journal of Medical Science, 2013)
Pyogenic granuloma is a benign, localized mass of exuberant granulation tissue produced in response to various stimuli. It is inflammatory hyperplasia of oral cavity commonly seen on gingival area and rarely on other parts of oral cavity such as lips, tongue, palate and buccal mucosa. It is seen predominantly in 2nd to 3rd decade of life in young females. Clinically manifesting as small red erythematous exophytic lesion, it must be biopsied to rule out other serious conditions. This article aims to present three cases of extra gingival pyogenic granulomas occurring in rare sites such as buccal mucosa, anterior hard palate and alveolar mucosa of completely edentulous ridge in maxilla. Pyogenic granuloma on buccal mucosa and anterior hard palate were seen in female patients with age of 40 years and 34 years respectively and pyogenic granuloma on alveolar mucosa of edentulous ridge in maxilla was noted in 70 years old male patient. Surgical excision was performed for all the lesion and follow up of one year did not show any recurrence. Please add little description of patient + treatment + followup results. DOI: http://dx.doi.org/10.3329/bjms.v12i4.16667 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 445-448